2013
DOI: 10.1111/nmo.12295
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic gut effect prevents the chronic psychological stress‐induced brain activity abnormality in mice

Abstract: These data suggest that chronic stress-induced abnormal brain plasticity and reduction in neurogenesis can be prevented by a pretreatment with the Probio'Stick(®) formulation, suggesting that probiotics modulate neuroregulatory factors and various signaling pathways in the central nervous system involved in stress response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
255
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(266 citation statements)
references
References 54 publications
4
255
0
7
Order By: Relevance
“…These findings are supported by our previous study showing that the combination of the 2 probiotics attenuates the stress response by modulating neuronal plasticity in specific brain areas. 25 The effect of B.longum or L. helveticus probiotic treatment on the adverse stressful events, particularly on the visceral pain induced by chronic stress, depends on the glucocorticoid negative feedback regulation of the HPA axis. Finally, the combination of 2 probiotics (B. longum and L. helveticus) has a better antinociceptive effect than the probiotic alone (B. longum or L. helveticus).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are supported by our previous study showing that the combination of the 2 probiotics attenuates the stress response by modulating neuronal plasticity in specific brain areas. 25 The effect of B.longum or L. helveticus probiotic treatment on the adverse stressful events, particularly on the visceral pain induced by chronic stress, depends on the glucocorticoid negative feedback regulation of the HPA axis. Finally, the combination of 2 probiotics (B. longum and L. helveticus) has a better antinociceptive effect than the probiotic alone (B. longum or L. helveticus).…”
Section: Discussionmentioning
confidence: 99%
“…25 Briefly, the mice were placed individually during a 1-hour period on a plastic platform positioned in the middle of a basin filled with room temperature water. The procedure was repeated for 4 consecutive days.…”
Section: Chronic Stress Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous animal studies have demonstrated that the administration of probiotics maintains mucosal barrier function under stressful situations (6,7) and mitigates stress-induced glucocorticoid and inflammatory cytokine responses in association with a reduction of depression-and anxiety-related behavior (7)(8)(9)(10)(11)(12). Probiotics have also been shown to reduce the mRNA expression of the gamma-aminobutyric acid (GABA) receptor and c-Fos in the brain (10,12), possibly by modulating the gut-brain axis via vagal pathways (10,11). Clinical trials have demonstrated that probiotics have beneficial effects by alleviating psychological distress in healthy subjects (9) and normalizing the stress-induced reduction of natural killer (NK) cell numbers (13) and gastrointestinal symptoms (14).…”
mentioning
confidence: 99%
“…Further indications of microbiota influence on brain processes and behaviors have come from reports showing that probiotics attenuated anxiety-like and depressive-like behaviors and limited plasma corticosterone elevations and IL-10 reductions as well as the hippocampal monoamine (5-HT and NE) reductions elicited by a chronic restraint stressor in rats [41]. Probiotics also prevented impairments of neurogenesis and BDNF changes elicited by stressors [42].…”
Section: Microbiota-gut-brain Axis and Links With Stress-related Disomentioning
confidence: 96%